Students' Perceptions on Biology Learning in the Senior High School - Yulisa, Yulisa; Suryanti, Suryanti (Universitas Sultan Ageng Tirtayasa, 2023)
This study aimed to determine students' perceptions on the implementation of biology learning in school. This research was quantitative research which uses a survey method. Data collection was carried out using questionnaires, interviews, observation, and documentation. The sample in this study were 128 students. The distributed questionnaire consisted of 35 statements. Based on the results of the study, the perceptions of science class of grade 10 students towards the implementation of biology learning were in very good category on preliminary activity indicators and good category on the core activity indicator and closing activities. It can be concluded that the average student perception of the implementation of biology learning in science class of grade 10 students was in the very good category with a percentage of 83.17%.